Ethics, equity, and inclusive education - Gajewski, Agnes; Forlin, Chris (International perspectives on inclusive education ;, 2017)
This volume focuses on professional ethics and the moral dimensions of inclusive education. The significance of ethics in inclusive education has been noted by numerous scholars, however, to date, a comprehensive review does not exist in the field. Grounded in an examination of international conceptualizations of ethics and inclusion, this book provides a comprehensive analysis of current understandings of professional ethics in the context of inclusive education and the many issues associated with its practice. The first chapters provide an overview of ethics and inclusive education, including; discussions on inclusion as ethical in nature based on an argument of inclusion as a human right; an examination of ethics and epistemology as it relates to inclusion; and the role of administrators in ethical practice. The second section focuses on practical issues related to ethical challenges, issues, and dilemmas in inclusive classrooms and teaching practice. The roles of the teacher, the co-teacher, and colleagues, which include administrators, specialists, and staff, are examined. Moreover, practice related problems are discussed including assessment, emergent curriculum, and meeting the needs of gifted learners in inclusive settings.